2017
DOI: 10.1521/pdps.2017.45.4.475
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Figure's Regulation of Infant Brain and Behavior

Abstract: Altricial infants (i.e., requiring parental care for survival), such as humans and rats, form an attachment to their caregiver and receive the nurturing and protections needed for survival. Learning has a strong role in attachment, as is illustrated by strong attachment formed to non-biological caregivers of either sex. Here we summarize and integrate results from animal and human infant attachment research that highlights the important role of social buffering (social presence) of the stress response by the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 177 publications
(241 reference statements)
0
7
0
1
Order By: Relevance
“…The quality of early relationships with attachment figures represents the main developmental environment for children's emotional regulation and related behaviors [104,105]. Biological studies have also highlighted the significant influence of attachment in the development of neuronal structures primarily involved in emotional regulation (i.e., amygdala, and hippocampus) [106,107]. If attachment figures respond to children's needs and emotional states with sensitivity and responsivity, individuals' ability to regulate emotions will be enhanced by the development of a secure attachment.…”
Section: Indirect Effects Of Attachment To Parents and Peers Via Alexithymiamentioning
confidence: 99%
“…The quality of early relationships with attachment figures represents the main developmental environment for children's emotional regulation and related behaviors [104,105]. Biological studies have also highlighted the significant influence of attachment in the development of neuronal structures primarily involved in emotional regulation (i.e., amygdala, and hippocampus) [106,107]. If attachment figures respond to children's needs and emotional states with sensitivity and responsivity, individuals' ability to regulate emotions will be enhanced by the development of a secure attachment.…”
Section: Indirect Effects Of Attachment To Parents and Peers Via Alexithymiamentioning
confidence: 99%
“…Beyond differing motivations, developmental change in exploration might also reflect differences in the ecology and value structure of childhood versus adulthood (Gopnik et al, 2017). In particular, the young of many species are often "protected" from the risks of everyday life; for example, attachment to a caregiver allows a young learner to explore novel (Sullivan, 2017) or aversive (Tottenham et al, 2019) environments that they would avoid otherwise.…”
Section: Exploration and Learning 41mentioning
confidence: 99%
“…Many studies using conditioning paradigms in neonatal rodents have therefore used olfactory cues as the CS ( Jovanovic et al, 2013 ). Elegant studies have shown that during the first 2 weeks of postnatal life in rats, the mother has the ability to modify the emotional valence of stimuli ( Moriceau and Sullivan, 2006 ; Santiago et al, 2017 ; Sullivan, 2017 ) even though pups can learn aversive responses after PND10. Before that time, PND8 rats are able to pair an odor and a foot shock (US), but the conditioned response is approach rather than avoidance to the shock ( Sullivan et al, 2000 ).…”
Section: Amygdala-prefrontal Cortex Development In Humans and Rodentsmentioning
confidence: 99%